2000
DOI: 10.1042/bj3520827
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic palmitoylation of lymphoma proprotein convertase prolongs its half-life, but is not essential for trans-Golgi network localization

Abstract: Proprotein convertases are responsible for the endoproteolytic activation of proproteins in the secretory pathway. The most recently discovered member of this family, lymphoma proprotein convertase (LPC), is a type-I transmembrane protein. Previously, we have demonstrated that its cytoplasmic tail is palmitoylated. In this study, we have identified the two most proximal cysteine residues in the cytoplasmic tail as palmitoylation sites. Substitution of either cysteine residue by alanine interfered with palmitoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…This region of ϳ25 amino acids contains the two cysteines that are reversibly palmitoylated (10). However, these cysteines have been shown to affect the half-life of PC7 but not its TGN localization (11). Another remarkable feature is the presence of seven basic amino acids near these cysteines, of which five are clustered in the sequence HRSRKAK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This region of ϳ25 amino acids contains the two cysteines that are reversibly palmitoylated (10). However, these cysteines have been shown to affect the half-life of PC7 but not its TGN localization (11). Another remarkable feature is the presence of seven basic amino acids near these cysteines, of which five are clustered in the sequence HRSRKAK.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression studies have shown partial co-localization with TGN markers, but a less confined expression pattern (10,11). Ultrastructural analysis showed immunoreactivity associated with coated buds and vesicles adjacent to the Golgi stack.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PC7 also undergoes a number of post-translational modifications, including N-glycosylation (5) and cytosolic tail Cys-palmitoylation (8). However, the zymogen activation mechanism is still unknown, as this requires exit of the prosegment-PC7 complex from the ER and/or separation of the inhibitory prosegment from mature PC7.…”
mentioning
confidence: 99%